Aetiological spectrum, clinical differentiation and efficacy of polyethylene glycol over lactulose in children with constipation: Experience of 316 cases. (26th June 2018) - Poddar, Ujjal; Singh, Sumit; Pawaria, Arti; Srivastava, Anshu; Yachha, Surender K
Abstract : Aim: To find the aetiological spectrum, clinical features to differentiate organic from functional constipation (FC) and the efficacy of polyethylene glycol (PEG) over lactulose in the treatment of childhood constipation. Methods: From January 2007 to December 2014, 316 consecutive children (up to 18 years) with constipation were included in this study. FC was defined as per Rome III criteria. Standard treatment protocol (disimpaction with PEG followed by laxatives) was followed in FC. Lactulose was used in the first 4 years of study and PEG in the last 4 years. Success of therapy was assessed at 3 months. Results: The median age was 44 (25.00–78.00) months, and 227 (72%) were boys. The majority, 245 (77.5%), had FC, while Hirschsprung disease was the most common organic cause (39.4%). On multivariate analysis, delayed passage of meconium, growth failure, absence of retentive posturing and absent faecal impaction significantly ( P < 0.05) determined an organic aetiology. In FC, successful outcome at 3 months was achieved equally with PEG and lactulose (81 vs. 76%, respectively). However, more children in lactulose group had to be switched over to PEG due to lack of efficacy ( P = 0.0002). Conclusions: FC is the most common cause of constipation in children. Presence of delayed passage of meconium, growth failure and absence of retentive posturing and absent faecal impaction raise the suspicion of an organic cause. Both lactulose and PEG are equally effective. PEG has an edge over lactulose as the need for switch over was uncommon.